Association of psychologist and its influence to psychology development in Lithuania - Lapė, Juvencijus (Psichologija, 1999)
The article offers an overview of the milestones in Lithuanian Association of Psychologists foundation and development history. Spheres of activity organised conferences, workshops and other events are described. The association influence to the development of psychology in Lithuania is highlighted.